Characterization, treatment patterns, and patient-related outcomes of patients with Fragile X syndrome in Germany: final results of the observational EXPLAIN-FXS study. Issue 1 (December 2016) - Haessler, Frank; Gaese, Franziska; Huss, Michael; Kretschmar, Christoph; Brinkman, Marc; Peters, Helmut; Elstner, Samuel; Colla, Michael; Pittrow, David
Abstract Background As data on the phenotype, characteristics and management of patients with Fragile X Syndrome (FXS) are limited, we aimed to collect such data in Germany in experienced centres involved in the treatment of such patients. Methods EXPLAIN-FXS is a prospective observational (non-interventional) study (registry) performed between April 2013 and January 2016 at 18 sites in Germany. Requirements for patient participation included confirmed diagnosis of FXS by genetic testing (>200 CGG repeats) and written informed consent. Patients were followed for up to 2 years. Results Seventy-five patients (84.0 % males, mean age 16.7 ± 14.5 years, ranging from 2 - 82 years) were analysed. The mean 6-item score, determined according to Giangreco (J Pediatr 129:611-614, 1996), was 6.9 ± 2.5 points. At least one neurological finding each was noted in 53 patients (69.7 %). Specifically, ataxia was noted in 5 patients (6.6 %), lack of fine motor skills in 40 patients, (52.6 %), muscle tonus disorder in 4 patients (5.3 %), and other neurological disorders in 39 patients (51.3 %). Spasticity was not noted in any patient. Seizures were reported in 6 patients (8.1 %), anxiety disorders in 22 patients (30.1 %), depression in 7 patients (9.6 %), ADHD/ADD in 36 patients (49.3 %), impairment of social behavior in 39 patients (53.4 %), and other comorbidities in 23 patients (31.5 %). The mean Aberrant Behaviour Checklist Community Edition (ABC-C) score on behavioral symptoms, obtained in 71 patients at first documentation, was 48.4 ± 27.8 (median 45.0, range 5-115). The mean visual analogue scale (VAS) score, obtained in 59 patients at first documentation, was 84.9 ± 14.6 points (median 90; range 50 – 100). Conclusions This report describes the largest cohort of patients with FXS in Europe. The reported observations indicate a substantial burden of disease for patients and their caregivers. Based on these observations, an early expert psychiatric diagnosis is recommended for suspected FXS patients. Further recommendations include multimodal and multi-professional management that is tailored to the individual patient's needs. Trial registration The ClinTrials.gov identifier isNCT01711606 . Registered on 18 October 2012.